Structural and Functional Analysis of the Amphioxus IGFBP Gene Uncovers Ancient Origin of IGF-Independent Functions - Zhou, Jianfeng (Endocrine Society, 2013)
IGFs play key roles in regulating vertebrate development, growth, reproduction, and aging. In extracellular fluids, IGFs are bound and regulated by a family of IGF-binding proteins (IGFBPs). Although all known IGFBPs are secreted proteins, some are also found in the nucleus and possess IGF-independent activities. When and how these distinct modes of biological actions have evolved is unknown. In this study, we identified and analyzed an IGFBP gene from amphioxus. Amphioxus shares a common ancestor with the modern vertebrate lineage that dates back to more than 520 million years ago. The amphioxus IGFBP shares all major structural characteristics of vertebrate IGFBPs. Phylogenetic analyses place it in a basal position in the IGFBP lineage. Ligand blot analysis reveals that amphioxus IGFBP does not bind to IGF-I or -II. Changing its Phe70 into Leu, however, is sufficient to convert it into a functional IGF binder. When tested in cultured cells, amphioxus IGFBP is localized in the nucleus, and this is attributed to 2 redundant nuclear localization sequences in its L domain. Furthermore, the amphioxus IGFBP N-terminal domain has strong transcriptional activation activity. Forced expression of amphioxus IGFBP in zebrafish embryos results in dorsalized phenotypes. This action requires nuclear localization. These results suggest that the nuclear localization and transcription activation activity of IGFBPs are ancient functions and the IGF-binding function may have been acquired by opportunistic gain-of-functional mutations later in evolution.